2010
DOI: 10.4321/s1886-36552010000200009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists´ participation in the documentation of medication history in a developing setting: An exploratory assessment with new criteria

Abstract: ObjectiveTo assess the impact of pharmacists’ participation on the frequency and depth of medication history information documented in a developing setting like NigeriaMethodThe study consisted of two phases. The first phase was a baseline cross-sectional assessment of the frequency and depth of medication history information documented by physicians in case notes of systematic samples of 900 patients that were stratified over 9 Medical outpatients Units at a premier teaching hospital in south western Nigeria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The second most common discrepancy we found was due to OTC and herbal medications that needed to be added to the medication list, which was also seen in other outpatient studies. 6 , 7 , 9 , 10 , 13 This is concerning due to the potential for numerous drug-drug and drug-disease interactions with OTC and herbal products, particularly in patients who are self-treating without the knowledge of their primary care physician. There were also a significant number of prescription medications from outside providers which needed to be documented in the medication list.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most common discrepancy we found was due to OTC and herbal medications that needed to be added to the medication list, which was also seen in other outpatient studies. 6 , 7 , 9 , 10 , 13 This is concerning due to the potential for numerous drug-drug and drug-disease interactions with OTC and herbal products, particularly in patients who are self-treating without the knowledge of their primary care physician. There were also a significant number of prescription medications from outside providers which needed to be documented in the medication list.…”
Section: Discussionmentioning
confidence: 99%
“…Yusuff and colleagues noted that pharmacist involvement significantly increased the quality and quantity of medication information that was documented. 13 An inpatient study led by Mergenhagen compared medication reconciliation by pharmacists to physicians and found that medication reconciliation by pharmacists was more comprehensive and led to lower odds of adverse drug events related to admission prescribing changes. 14 Another inpatient study by Lancaster and colleagues demonstrated the value of student pharmacists in the inpatient reconciliation process.…”
Section: Introductionmentioning
confidence: 99%
“…In an outpatient study performed in Nigeria by Yusff and colleagues, pharmacist involvement in medication histories for 324 patients significantly increased the frequency and depth of medication information documented 9. Documentation of prescription drugs increased from 68.9% at baseline to 100% after pharmacist intervention, over-the-counter medication documentation increased from 25.1% to 96.9%, and herbal drug use documentation increased from 10.7% to 85.5% (p=0.0001 for all).…”
Section: Introductionmentioning
confidence: 97%
“…Health professionals should document appropriately to minimize or eliminate medication errors. Pharmacists' participation in medication history documentation might significantly increase the frequency and depth of medication history information documented [24]. UNTH had more interventions and known outcomes of interventions than Medical Centre.…”
Section: Resultsmentioning
confidence: 99%